Spectral approximation methods for Fredholm integral equations with non-smooth kernels - Allouch, Chafik; Sbibih, Driss; Tahrichi, Mohamed (Mathematical modelling and analysis, 2022)
In this paper, polynomially based projection and modified projection methods for approximating the solution of Fredholm integral equations with a kernel of Green’s function type are studied. The projection is either an orthogonal projection or an interpolatory projection using Legendre polynomial basis. The orders of convergence of these methods and those of superconvergence of the iterated versions are analysed. A numerical example is given to illustrate the theoretical results.